Promoting Positive Relationship Between Parents and Grandparents: A Randomized Controlled Trial of Group Triple P Plus Compassion in Vietnam. Issue 6 (November 2022) - Hoang, Nam-Phuong T.; Kirby, James N.; Haslam, Divna M.; Sanders, Matthew R.
Highlights: Triple P+ compassion was effective in reducing parent-grandparent conflict. Parental self-compassion increased post-intervention. Dysfunctional parenting and child behavioral problems decreased post-intervention. Child prosocial behaviors increased steadily post-intervention and at follow-up. Parents reported high levels of program satisfaction. Abstract: In Vietnamese culture, grandparents are significantly involved in the upbringing of grandchildren. This involvement of grandparents entails lots of ambiguities and challenges. Boundaries between parents and grandparents are often unclear, and communication can be restricted due to power differentials, leading to inconsistent discipline. This study seeks to evaluate the efficacy of the Group Triple P–Positive Parenting Program plus Building Coparenting Alliance—a compassion-focused module to promote the parent-grandparents relationship. One hundred Vietnamese parents whose parents or parent in-laws provided care for their children were randomly assigned to either an intervention condition ( n = 50) or a waitlist control condition ( n = 50). Both groups were assessed at three time-points (pre-intervention, post-intervention, and 6-month follow-up). The short-term intervention effects were found across domains, including co-parenting conflict, parents' self-compassion, dysfunctional parenting, parenting self-efficacy, parental adjustment, child behavioral problems and child prosocial behaviors. Intervention effects on co-parenting conflict, parenting behaviors, and the child's prosocial behaviors were maintained at a 6-month follow-up. This study demonstrates the efficacy of Triple P plus compassion in promoting co-parenting relationships between parents and grandparents, enhancing parenting practice and child outcomes in Vietnamese families.